Qualitative Study of Factors Influencing Adherence of People With HIV/AIDS in ARV Consumption in Cilacap Regency - Johariyah, Johariyah; Apriani, Evy (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
The quality of life of HIV/AIDS people depends on the consumption of antiretroviral drugs. The viral load control response of 85% requires a commitment of 90-95% drug use. If the patient takes ARV 60 times a month, the patient does not miss more than 3 doses. The study aimed to look for factors influencing the compliance of People living with HIV/AIDS with ARV consumption. The research was conducted through qualitative research through in-depth interviews as a data collection technique for five PLHIV and their families, and interviews with peer group support, the Management of the Cilacap Regency AIDS Mitigation Commission, and the Head of VCT Cilacap Hospital carried out triangulation.  Data processing techniques were carried out using thematic analysis. Based on the analysis results, 4 themes were obtained: factors that affect the compliance of PLHIV in ARV consumption as follows: internal factors: 1) Reluctance to drink because of boredom; 2). Irregularity of drinking due to forgetfulness; 3). Unwillingness to take ARV because they feel no complaints and external factors: 4) There is still a stigma against PLHIV in the community.